Anxiety, sleep quality and mood in elite athletes during the COVID-19 pandemic: a preliminary study - Soares, L. L.; Leite, L. B.; Guilherme, L. Q.; Rezende, L. M.; Noce, F.; Pussieldi, G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The social isolation (quarantine) caused by COVID 19 has generated several consequences for the physical and mental health of the general population, however little is known about the effects of this disease on elite athletes. We seek to assess the effect of social isolation on anxiety, sleep quality and quality of life for elite athletes. METHODS: 206 athletes from collective and individual sports (116 men and 90 women) participated in the present study, with an average age of 24.61 ± 8.73 years. Time devoted to physical training before and during the pandemic was assessed. Assessment of anxiety symptoms, sleep quality and mood were assessed using semi-structured questionnaires. RESULTS: There was a reduction in hours dedicated to training, as well as in training sessions for both groups evaluated. There is a high prevalence (> 90%) of anxiety symptoms (medium and high) in both groups. There were no major losses in the sleep quality of the athletes (> 75% presented regular to very good sleep). CONCLUSIONS: There are no differences regarding the traits and state of anxiety between athletes of collective and individual modalities. However, both groups showed traces of anxiety, which, from the point of view of health, becomes worrying.